Does the frequency of switching inhalers represent a predictive factor of exacerbation in asthma? - Principe, Stefania; Battaglia, Salvatore; Benfante, Alida; Arena, Cinzia; Scichilone, Nicola (The Journal of asthma, 2022)
Management of asthma includes monitoring of inhaler technique and level of adherence to treatment. Both factors could be influenced by high frequency of switching inhaler devices. We explored whether switching inhalers is an independent predictive factor of exacerbations. Data were collected from 2015 to 2017 from the outpatient clinic of asthma at the University of Palermo, Italy. This observational study consisted of two phases: Phase 1 included subjects of at least three visits in the previous year who reported the frequency of inhalers switched; Phase 2 included subjects of at least two visits during the second year, and the rate of switches and exacerbations was recorded. We included adult (24-84 years old) mild/moderate asthmatics under regular inhaled treatment; uncontrolled asthma was defined as poor symptom control, exacerbations (≥2/year) requiring oral corticosteroids (OCS), or serious exacerbations (≥1/year) requiring hospitalization. A total of 109 records were retrieved for the analysis. A significant correlation between the rate of switches in Phase 1 and exacerbations in Phase 2 was found (p = 0.001). Age and the rates of exacerbations in Phase 1 were also independently associated with a higher number of exacerbations in Phase 2 (p < 0.0001). The multivariate regression model showed that the numbers of switches, as well as exacerbations in Phase 1, were independently correlated to the number of exacerbations in Phase 2 (p = 0.003). The frequency of switching inhalers independently affects the risk of exacerbations in asthma. These results imply that changing inhaler requires careful management in clinical practice.